Reassessing the centipede fauna of the Paiko–Pinovo–Tzena–Voras mountain range in the southern Balkans - Simaiakis, Stylianos M.; Kos, Anja; Georgopoulou, Elisavet; Stojanović, Dalibor Z. (Zootaxa, 2026)
The first critically revised catalogue of the centipede fauna of the Paiko, Pinovo, Tzena and Voras mountains in northern Greece is presented. A total of 34 centipede species are listed, belonging to 13 genera, six families and four orders. The highest diversity was recorded within the order Lithobiomorpha (20 species), dominated by species of the genus Lithobius Leach, 1814 (14 species), followed by the order Geophilomorpha (10 species). The species Lithobius karamani Verhoeff, 1937 and Clinopodes skopljensis (Verhoeff, 1938) are here reported for the first time from Greece. The genera Scutigera, Cryptops, Himantarium, Bothriogaster, Henia and Geophilus were recorded for the first time in the fauna of the study area. Twenty-one out of the 34 species are newly reported from the studied mountainous area, including Scutigera coleoptrata, Eupolybothrus zeus, E. werneri, Lithobius forficatus, L. latro, L. lucifugus, L. muticus, L. peregrinus, L. crassipes, L. microps, Cryptops hortensis, C. parisi, Scolopendra cingulata, Himantarium gabrielis, Bothriogaster signata, Henia devia, H. illyrica, Clinopodes carinthiacus and Geophilus carpophagus. South European, European, Balkan, and endemic faunal elements predominate among the identified taxa. For each species, information is provided on distribution within the northern Greek mountain range, habitat preferences, altitudinal range, and relevant taxonomic notes. In addition, we assessed whether the sites where the species were recorded are included in the Natura 2000 Network; the conservation status of all species is reported, together with distribution maps for northwestern Greece.